2014
DOI: 10.1371/journal.pone.0112470
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Stimulates Hypoxia-Inducible Factor-1 Activity in Tumor Cells by Initiating the ROS/Akt/p70S6K Signaling Pathway and Enhancing Hypoxia-Inducible Factor-1α Protein Synthesis

Abstract: Celastrol, a tripterine derived from the traditional Chinese medicine plant Tripterygium wilfordii Hook F. (“Thunder of God Vine”), has been reported to have multiple effects, such as anti-inflammation, suppression of tumor angiogenesis, inhibition of tumor growth, induction of apoptosis and protection of cells against human neurodegenerative diseases. However, the mechanisms that underlie these functions are not well defined. In this study, we reported for the first time that Celastrol could induce HIF-1α pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…There are, however, emerging findings suggesting that cellular HIF levels may also be regulated at normal oxygen tensions either by changes of HIF gene transcription, by endogenous modulation of PHD activity, or by endogenous modulation of HIF-protein degradation. [59][60][61][62][63][64] If and how those oxygen-independent modulations of cellular HIF-2 levels could be relevant for the glomerular endocrine switch from renin to EPO expression remains to be clarified. Another important aspect in this context that awaits clarification is whether the HIF-2-induced glomerular endocrine switch is reversible.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, emerging findings suggesting that cellular HIF levels may also be regulated at normal oxygen tensions either by changes of HIF gene transcription, by endogenous modulation of PHD activity, or by endogenous modulation of HIF-protein degradation. [59][60][61][62][63][64] If and how those oxygen-independent modulations of cellular HIF-2 levels could be relevant for the glomerular endocrine switch from renin to EPO expression remains to be clarified. Another important aspect in this context that awaits clarification is whether the HIF-2-induced glomerular endocrine switch is reversible.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor-1 (HIF-1), a master regulator of gene expression induced by hypoxia, serves an important role in the origin and development of HPH (9). A recent study has demonstrated that ROS serve an important role in the regulation of HIF-1 expression and activity (10).…”
Section: Introductionmentioning
confidence: 99%
“…These results support the negative regulation of AR on celastrol-induced autophagy that was found in AR positive cells. It has been reported that celastrol induces autophagy in AR negative prostate cancer cell line such as PC-3 as well as other type of cancers such as pancreatic cancer and hepatocarcinoma [ 21 , 22 ]. Activation of HIF-1/BNIP3 has been proved to be a mechanism for celastrol to induce autophagy in those types of cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%